IMPLEMENTASI IMPROVING LEARNING DENGAN METODE DRILL MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Muhardi muharday (Asaatidzah, 2023)
This class action research is motivated by the low activeness of learners in following learning and there are still many learners who have not been completed on the material of gratitude prostration, sahwi prostration and prostration tilawah. This research aims to improve the learning outcomes of Islamic Religious Education on the material of the procedure of prostration of gratitude, prostration of sahwi and prostration of tilawah, by applying the implementation of improving learning with drill methods. The type of research is Class Action Research with two cycles from October to December 2021, located in class VIII B of State Junior High School 02 Pontianak. The techniques and data collection tools in this study use descriptive analysis techniques on data in the form of student work documents, score lists and observation sheets. The results showed that with the drill method becomes a pleasant learning atmosphere so that the learning outcomes of learners increase, namely from the results of cycle I to Cycle II there is an increase. It was concluded that the drill method can improve students' learning outcomes.